Generational Differences in Emoji Interpretation: A Study of Millennial, Gen Z, and Baby Boomers - Tehreem Zahra; Soban Ahmed (`, 2025)
Today, using emojis makes it easier to add emotion, tone and what you intend to say in messages. Still, given that emojis are understood differently by age groups, there is a chance for misunderstandings. This paper looks into how emojis are interpreted differently by members of the millennial generation, Gen Z and the Baby Boomers. To understand how each generation views common emojis, we use surveys, gather discussions in focus groups and analyze how they are used on the internet. It is revealed by our study that while Gen Z might mean something else with emojis, Millennials seem to take them at face value and Baby Boomers tend to use them plainly. According to the study, emojis such as thumbs up, crying laughing and skull are more likely to cause mix-ups between generations. Such examples illustrate that digital language is changing and that culture and generation matter in online communication. They relate to digital literacy, how people from different generations communicate and the creation of platforms designed for all ages. Keywords: Emoji, Interpretation, Gen Z, Baby Boomers, Thumbs Up, Digital Literacy